2008
DOI: 10.1037/a0014223
|View full text |Cite
|
Sign up to set email alerts
|

Altruism born of suffering: The roots of caring and helping after victimization and other trauma.

Abstract: Research on altruism has focused on its positive roots, whereas research on the effects of victimization and suffering has focused on aggression and difficulties in functioning. However, anecdotal evidence, case studies, and some empirical research indicate that victimization and suffering can also lead people to care about and help others. This article examines the relation of "altruism born of suffering" to resilience and posttraumatic growth, and proposes potentially facilitating influences on altruism born… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
313
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(335 citation statements)
references
References 100 publications
21
313
1
Order By: Relevance
“…This hypothesis was not, however, supported in the 743 swimmers' highly individualistic accounts but an alternative explanation may be that they 744 experienced an increased awareness of pain and suffering, which stimulated feelings of empathy 745 and responsibility, and resulted in a commitment to helping others (cf. Staub & Vollhardt, 2008 A noteworthy strength of this study is the use of autobiographies that span top sport 767 performers' lives and provide valuable and privileged insights into psychosocial processes and 768 changes. Notwithstanding this strength, these accounts are influenced by the writers' motives and 769 biases, their ability to recall events and experiences, and others' expectations and potential 770 judgments.…”
Section: Results and Discussion 311mentioning
confidence: 99%
“…This hypothesis was not, however, supported in the 743 swimmers' highly individualistic accounts but an alternative explanation may be that they 744 experienced an increased awareness of pain and suffering, which stimulated feelings of empathy 745 and responsibility, and resulted in a commitment to helping others (cf. Staub & Vollhardt, 2008 A noteworthy strength of this study is the use of autobiographies that span top sport 767 performers' lives and provide valuable and privileged insights into psychosocial processes and 768 changes. Notwithstanding this strength, these accounts are influenced by the writers' motives and 769 biases, their ability to recall events and experiences, and others' expectations and potential 770 judgments.…”
Section: Results and Discussion 311mentioning
confidence: 99%
“…Recently, the prosocial effects of stress have also been underscored through a series of studies that identified the phenomenon termed "altruism born of suffering" 191 . Specifically, these studies revealed increased motivation in former victims of suffering (whether from natural causes or inflicted by other human beings) to help others -particularly in-group members -and prevent further suffering 172,191 .…”
Section: Box 1 Stress and Social Behaviors In Humansmentioning
confidence: 99%
“…Therefore, it is expected that the links between social class and prosocial orientation are in line with the notion that experiencing adversity fosters prosociality [19,20].…”
Section: Social Class and Prosocial Orientationmentioning
confidence: 75%
“…That is, those who sufered may often choose to provide social or informational support instead of tangible material support. Moreover, the driving force behind such preferences for prosociality may not be driven by empathy but instead by other mechanisms such as self-other similarity or communal orientation [16,20].…”
Section: A General Model Of Sufering and Prosocial Growth Via Empathymentioning
confidence: 99%